Response to Drs. Bramson and Guay’s Comments on the Proposed Pediatric Oral Health Therapist - David A. Nash, DMD, MS, EdD (Blackwell Synergy, 2005)
I am pleasantly surprised to have had the Executive Director of the American Dental Association (ADA), Dr. Bramson, and the Association’s Associate Director for Policy, Dr. Guay, respond to the article on adding a pediatric oral health therapist to the dental team; surprised in that the ADA, as an organization, does not customarily respond to articles in the dental literature, and pleasantly so in that it suggests (to me) that possibly the leadership of the ADA is concerned that the proposal could gain traction in the United States-as it has in over 40 countries in the world.